2012
DOI: 10.1016/j.concog.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Nonconscious perception, conscious awareness and attention

Abstract: Because it is unclear how a nonconscious stimulus is cognitively processed, there is uncertainty concerning variables that modulate the processing. In this context recent findings of a set of neuroimaging experiments are important. These findings suggest that conscious and nonconscious stimuli activate same areas of the brain during performance of a similar task. Further, different areas are activated when a task is performed with or without awareness of processing. It appears that the neural network involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…These studies have consistently found attenuated activity in the extrastriate cortex during nonconscious retrieval of incidentally encoded stimuli [1825]. In a series of neuroimaging experiments we found that the attenuation is located in a small extrastriate area called V3A [21,23,2628]. This is a unique area because even though it is located in the visual cortex [close to the parieto-oc cipito-temporal junction], it receives input from all sensory modalities and its morphological and neurochemical characteristics are different from those of the other visual processing areas [29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies have consistently found attenuated activity in the extrastriate cortex during nonconscious retrieval of incidentally encoded stimuli [1825]. In a series of neuroimaging experiments we found that the attenuation is located in a small extrastriate area called V3A [21,23,2628]. This is a unique area because even though it is located in the visual cortex [close to the parieto-oc cipito-temporal junction], it receives input from all sensory modalities and its morphological and neurochemical characteristics are different from those of the other visual processing areas [29].…”
Section: Discussionmentioning
confidence: 99%
“…Since the difference between the conscious and nonconscious conditions is awareness of retrieval, it was suggested that the late attenuation of the V3A activity and increased frontal activity are associated with conscious awareness. Further, coincidence of the timeline indicates that a feedback loop between the V3A and frontal cortex is activated during the processing that leads to conscious awareness of retrieved information [2628,30]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently identified this network by analyzing the pattern of neural activation elicited during processing of visual stimuli with or without conscious awareness [3-11]. In a series of neuroimaging experiments we studied conscious and nonconscious retrieval of visual stimuli and found that the activity in the area V3A located in the extrastriate cortex, is significantly attenuated during nonconscious processing.…”
mentioning
confidence: 99%